2019
DOI: 10.1053/j.gastro.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

HCV-Induced Epigenetic Changes Associated With Liver Cancer Risk Persist After Sustained Virologic Response

Abstract: infection is an important risk factor for hepatocellular carcinoma (HCC). Despite effective antiviral therapies, the risk for HCC is decreased but not eliminated after a sustained virologic response (SVR) to direct-acting antiviral (DAA) agents, and the risk is higher in patients with advanced fibrosis. We investigated HCV-induced epigenetic alterations that might affect risk for HCC after DAA treatment in patients and mice Gastroenterology 2019;156:2313-2329 BASIC AND TRANSLATIONAL LIVER with humanized livers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
257
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(267 citation statements)
references
References 41 publications
8
257
0
2
Order By: Relevance
“…Currently, no effective vaccine for HCV is available worldwide, which has greatly hampered the prevention of HCV infection and liver cancer due to hepatitis C. Although the treatment of HCV infection has progressed considerably as a result of the implementation of interferon‐free, direct‐acting antiviral (DAA)‐based combination therapies, the resistance of HCV to DAAs has played an important role in the failure of interferon‐free treatment regimens . Moreover, those fortunate enough to be cured of chronic hepatitis C with DAAs may remain at risk for liver cancer for an indefinite period . Consequently, the prevention of liver cancer due to hepatitis C should involve at least three aspects: (a) preventing widespread transmission of HCV among the general population, (b) continuously investing in the development of the HCV vaccine, and (c) strengthening programs for weight management and increasing the rate of antiviral treatment for HCV as these drugs become less expensive to procure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no effective vaccine for HCV is available worldwide, which has greatly hampered the prevention of HCV infection and liver cancer due to hepatitis C. Although the treatment of HCV infection has progressed considerably as a result of the implementation of interferon‐free, direct‐acting antiviral (DAA)‐based combination therapies, the resistance of HCV to DAAs has played an important role in the failure of interferon‐free treatment regimens . Moreover, those fortunate enough to be cured of chronic hepatitis C with DAAs may remain at risk for liver cancer for an indefinite period . Consequently, the prevention of liver cancer due to hepatitis C should involve at least three aspects: (a) preventing widespread transmission of HCV among the general population, (b) continuously investing in the development of the HCV vaccine, and (c) strengthening programs for weight management and increasing the rate of antiviral treatment for HCV as these drugs become less expensive to procure.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, those fortunate enough to be cured of chronic hepatitis C with DAAs may remain at risk for liver cancer for an indefinite period. 38,39 Consequently, the prevention of liver cancer due to hepatitis C should involve at least three aspects: (a) preventing widespread transmission of HCV among the general population, (b) continuously investing in the development of the HCV vaccine, and (c) strengthening programs for weight management and increasing the rate of antiviral treatment for HCV as these drugs become less expensive to procure. Alcohol use and NASH are widely known risk factors for the development of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed the loss of intrahepatic immune activation by IFNα after DAA therapy due to the decreased levels of chemokine C-X-C motif ligand 10 (CXCL10), CXCL11, and a rapid decrease in NK cell activation and a normalization of NK cell cytotoxic effector functions [48], leading to ineffective surveillance of neoplastic clones. Another possible explanation is the epigenetic changes that induce H3K27ac modifications by chronic hepatitis C infection, associated with increased HCC risk, which persists even after HCV cure by DAA therapy [49].…”
Section: Discussionmentioning
confidence: 99%
“…These two genes are important in HCC development since the functional knockout of these two genes has been shown to inhibit HCC growth. 325 A recent publication supports the data showing that SOX gene signatures are associated with the expression of liver cancer dedifferentiation markers. 327 The development of an oncogenic signature relates to SOX expression.…”
Section: Reversal Of Direct Mechanisms After Daas Treatmentmentioning
confidence: 55%
“…Two studies have used chromatin immunoprecipitation and DNA sequence analysis from chronic HCV patients with or without DAAs treatment. 325,326 Hamdane et al showed that the expression levels of 2 genes: sphingosine kinase 1 and SOX-2, a transcription factor, did not change after HCV cure. The expression levels of these two genes were examined in the samples of patients before and after HCV cure as well as HCV-induced HCC samples.…”
Section: Reversal Of Direct Mechanisms After Daas Treatmentmentioning
confidence: 99%